2021
DOI: 10.3389/fmed.2021.662358
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Risk Factors for Spontaneous Pneumomediastinum in COVID-19 Patients

Abstract: Background: Spontaneous pneumomediastinum (SPM) is an uncommon condition in COVID-19 patients. No information about outcome or risk factors is available at the time. The aim of this research is to report on the frequency and risk factors of spontaneous pneumomediastinum in COVID-19 patients.Materials and Methods: An unmatched case-control study was carried out in a tertiary health-care facility for patients with COVID-19. Electronic files were reviewed to identify patients with confirmed COVID-19 infection by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
1
12
1
5
Order By: Relevance
“…Eight studies reported the length of hospitalization (LoH) [ 1 , 9 , 11 , 12 , 14 , 15 , 18 , 21 ]. LoH was longer in COVID-19 patients in all studies than non-barotrauma COVID-19 patients, except Elsaaran H [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies reported the length of hospitalization (LoH) [ 1 , 9 , 11 , 12 , 14 , 15 , 18 , 21 ]. LoH was longer in COVID-19 patients in all studies than non-barotrauma COVID-19 patients, except Elsaaran H [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported in-hospital mortality [ 1 , 2 , 9 , 10 , 12 , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] ]. Total mortality was 58.7% in the barotrauma group compared to 40.6% in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of pneumomediastinum for the entire study period was found to be 4.42%. An incidence of 3.3% (9/271) was found in a study by Rodriguez-Arciniega et al looking at unenhanced CT scans 15. Kangas-Dick et al looked at incidence of pneumomediastinum in a cohort of 346 intubated patients with COVID-19 and found the incidence of 10% 16.…”
Section: Discussionmentioning
confidence: 97%
“…An incidence of 3.3% (9/271) was found in a study by Rodriguez-Arciniega et al looking at unenhanced CT scans. 15 Kangas-Dick et al looked at incidence of pneumomediastinum in a cohort of 346 intubated patients with COVID-19 and found the incidence of 10%. 16 This is comparable to the incidence of 11.34% (11/97) of pneumomediastinum in our cohort of ventilated (intubated and CPAP/NIV together) patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%